Applications of Nanomaterials in Membrane Separation for Effluent Treatment in the Textile Industry - Keka Rana (International Journal of Advance in Molecular Engineering, 2026)
The textile industry makes a significant contribution to economic growth. As the global population continues to increase exponentially, production rates are also on the rise to meet this growing demand. Unfortunately, this surge in production often leads to noncompliance with environmental regulations. While the textile industry supports economic development, it also contributes to serious pollution. Various dyes, such as azo dyes, Congo Red (CR), Crystal Violet, methylene blue, and methyl orange, are commonly used in textile manufacturing. These unused dyes frequently end up in effluents, polluting water bodies and soil. Furthermore, some of these dyes have carcinogenic effects, raising significant concerns among researchers. To address these issues, efforts are being made not only to remove these dyes but also to degrade them in order to mitigate the environmental problems they cause. Traditional methods such as adsorption and membrane separation have been widely used to address these serious environmental challenges, yielding notable results. However, the severity of these problems drives researchers to develop more advanced techniques aimed at improving removal efficiency. Nanomaterials play a significant role in this effort. Additionally, combining nanomaterials with membrane-based separation often enhance the effectiveness of the process. For example, titanium dioxide and graphene oxide nanocomposites integrated into polyethersulfone membranes demonstrate exceptional performance in treating raw textile wastewater. These composites exhibit better antifouling properties compared to standard virgin polyethersulfone membranes. Graphene oxide-silver nanocomposites also show remarkable outcomes in treating textile effluent. Furthermore, ceramic nanocomposite membranes are displaying promising performance in textile effluent treatment. Reports indicate that the removal efficiency is 95% for nano TiO2-bentonite ultrafiltration (UF) and nearly 100% for tight TiO2 UF. Ceramic hybrid hollow fiber membranes also show a removal efficiency of 99.3%. Therefore, nanomaterials play a decisive role in achieving remarkable treatment efficiency of textile effluent, ultimately benefiting the environment and the ecosystem, making it safer for living organisms.
Keywords: Ceramic; ZnO; graphene oxide; membrane; nanocomposite membrane; textile effluent